Gender-specific oxidative stress parameters - Dopsaj, V.; Martinovic, J.; Dopsaj, M.; Stevuljevic, J. K.; Bogavac-Stanojevic, N. (International Journal of Sports Medicine, 2011)
The aim of the present study was to examine the association of proteins that regulate iron transport/storage content and acute phase response with oxidative stress in male and female athletes. Serum ferritin, transferrin, soluble transferrin receptor, C-reactive protein, interleukin-6 and oxidative stress parameters (reactive oxygen metabolites, superoxide anion, advanced oxidation protein products, lipid hydroperoxides, superoxide-dismutase and pro-oxidant-antioxidant balance) were determined in 138 athletes (73 females and 65 males). A general linear model indicated significant gender differences between athletes in terms of reactive oxygen metabolites (307.48±61.02 vs. 276.98±50.08; P=0.030), superoxide-dismutase (114.60±41.64 vs. 101.42±38.76; P=0.001), lipid hydroperoxides (149.84±38.95 vs. 101.43±39.26; P<0.001), pro-oxidant-antioxidant balance (512.40±148.67 vs. 413.09±120.30; P=0.002), advanced oxidation protein products (1.49±0.30 vs. 0.91±0.25; P<0.001) and superoxide (2.61±0.36 vs. 2.22±0.35; P=0.001), which were all significantly higher in females. Multivariate analysis of covariance indicated gender (P<0.001), training experience (P=0.004), C-reactive protein (P=0.002), soluble transferrin receptor (P=0.004) and transferrin (P<0.001) as significant covariates. Gender accounted for the largest proportion of variability for all oxidative stress parameters (46.3%) and female athletes were more susceptible to oxidative stress. Iron transport and storage proteins (transferrin and ferritin), but also acute phase reactants, were negatively related factors for oxidative stress. In conclusion, variation in the ferritin level may contribute to the different oxidative stress level between the sexes.